2023
DOI: 10.1021/acsenergylett.3c00742
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Interfacial Passivations for FASnI3 Solar Cells with Co-Cations

Abstract: Seven cations, methylammonium (MA), ethylammonium (EA), aziridinium (AZ), dimethylammonium (DMA), 2-hydroxyethylammonium (HEA), imidazolium (IM), and guanidinium (GA), were used to cocrystallize with formamidinium (FA) to form cocationic tin perovskite solar cells (TPSCs) using a two-step fabrication procedure. Time-of-flight second ion mass spectrometry results indicate that the pristine FA-based TPSC involved both vacancies on the perovskite surface and perovskite/poly(3,4-ethylenedioxythiophene):poly(styren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, the acidic nature of PEDOT:PSS often hinders the crystal growth of perovskites and leads to the deterioration of IPSC device stability, while CPE is pH-neutral, which improves the crystal growth on top of perovskites. It can be predicted that they have great potential as ideal and effective interlayers for IPSC with various organic and inorganic HTLs. ,, Shen et al demonstrated the benefit of the amphiphilic molecule Triton X-100-modified NiO x as the HTL in IPSCs. Shen et al took full advantage of Triton: the hydrophilic part of the molecule with a large number of ether groups is chemically bound to Ni 3+ on the surface of the NiO x film, while the hydrophobic part protrudes from the NiO x film, protecting the device from water penetration like an umbrella (Figure d–g).…”
Section: The Interface Engineering Of Perovskite/htl Interfacementioning
confidence: 99%
“…Moreover, the acidic nature of PEDOT:PSS often hinders the crystal growth of perovskites and leads to the deterioration of IPSC device stability, while CPE is pH-neutral, which improves the crystal growth on top of perovskites. It can be predicted that they have great potential as ideal and effective interlayers for IPSC with various organic and inorganic HTLs. ,, Shen et al demonstrated the benefit of the amphiphilic molecule Triton X-100-modified NiO x as the HTL in IPSCs. Shen et al took full advantage of Triton: the hydrophilic part of the molecule with a large number of ether groups is chemically bound to Ni 3+ on the surface of the NiO x film, while the hydrophobic part protrudes from the NiO x film, protecting the device from water penetration like an umbrella (Figure d–g).…”
Section: The Interface Engineering Of Perovskite/htl Interfacementioning
confidence: 99%
“…Furthermore, Diau et al delayed the crystallization of films by introducing a two‐step method, and explored the effects of seven organic cations. [ 63 ] As a result, devices containing guanidinium (GA) showed the best performance, which can be attributed to the fact that GA can passivate vacancy defects on the surface and interface, and can also optimize film crystallization (Figure 4c). Chen et al further found that GAI can be used as ionic compensation to repair multi‐vacancy defects, optimize film quality, and prolong carrier lifetime.…”
Section: Strategies To Optimize Carrier Transport In Low‐dimensional ...mentioning
confidence: 99%
“…before entering the Energy Market. To accelerate the commercialization of PSCs, several methods have been employed for improving the device stability: PVK composition optimization [259][260][261][262][263][264][265], surface and interface passivation [259,[266][267][268][269][270][271], molecular design of carrier transport material [146,177,[272][273][274][275][276], electrode modification [277], and rational encapsulation [278,279], among others [81,280,281].…”
Section: Vapor Depositionmentioning
confidence: 99%